LOW FLOW ANESTHESIA WILL GAIN ERAS (ENHANCED RECOVERY AFTER SURGERY) - Senapathi, Tjokorda Gde Agung; Suarjaya, I Putu Pramana; Pradhana, Adinda Putra; Makmur, Eric (Bali Journal of Anesthesiology, 2017)
ABSTRACTÂ As we know, the volatile agent needs fresh gas flow to be carried out to the patient. It is very common in anesthesia practice, we use the fresh gas flow more than 2 liters per minute. In recent practice, the more flow we gave, the more volatile agent blew out to the patient. The present of APL (adjustable pressure limit) also leaks out of the circuit, we spend more gases, volatile agent, hence gave more pollutant to the operating theater. The consequences of those are an increase of anesthesia expenses and change the way of health care being delivered.ERAS (Enhanced Recovery After Surgery) is popular with its quick recovery after surgery, include quick emergence post anesthesia, that will reduce the time in the operating theater, recovery room, and as results, reduce the cost of anesthesia and surgery.Â